The impact of hyperventilation on seizure duration following electroconvulsive therapy: a systematic review and meta-analysis of randomized trials - Tianqi Shen; Xingxing Yin; Xiaomeng Yu; Haibo Song; Menglu Li; Xiangjie Li; Shan Qin (BMC Psychiatry)
Abstract Background Electroconvulsive therapy (ECT) is a treatment used for severe psychiatric conditions that involves the induction of seizures under general anesthesia. It has been proposed that hyperventilation, which is the rapid breathing either voluntary or induced to lower carbon dioxide levels, might have an impact on the effectiveness of ECT. This systematic review and meta-analysis aimed to consolidate the current evidence on how hyperventilation may alter the course and outcomes of ECT by potentially affecting seizure duration and the resultant therapeutic outcomes, and assess its implications for both safety and potential therapeutic outcomes for patients. Methods We conducted a systematic literature search of articles published up to April 18, 2024, in databases including PubMed, the Cochrane Library, Embase, Web of Science Core Collection, Ovid, Wanfang Data, the China National Knowledge Infrastructure, and the SINOMED database. Revised Cochrane Risk of Bias Tool for Randomized Trials (RoB 2.0) was used to evaluate the quality of these studies. Statistical analysis was conducted using RStudio version 4.3.2, with the Egger’s test for publication bias and sensitivity analysis for result robustness. Results Seven studies with 620 ECT sessions were analyzed. Hyperventilation significantly extended muscle (MD 2.880 s, 95% CI 0.917–4.842 s, GRADE moderate) and EEG (MD 5.426 s, 95% CI 0.656–10.195 s, GRADE moderate) seizure durations. No significant differences in safety indices were observed between groups. Additionally, the overall bias across the included studies was significant, and the majority of studies relied solely on seizure duration as an indicator of ECT efficacy. Conclusion Hyperventilation during ECT induction phase may improve seizure outcomes and is well-tolerated, though further research is needed to confirm these preliminary findings.